The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/contagri-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Fluorescence and Drought Tolerance in a Mapping Population of Durum Wheat

Abstract: Summary This study was conducted to compare and estimate the genetic variability among durum wheat lines in response to drought according to their grain yields and physiological traits. The use of fluorescence parameters as drought selection criteria for durum wheat was investigated in a population of 249 recombinant inbred lines (RILs) derived from a cross between two cultivars of durum wheat: ‘Svevo’ and ‘Kofa’. The durum wheat RILs considered were analyzed to determine the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…In the presence of drought stress, crucial parameters for photosynthesis in tomato plants, such as Fv/Fm and chlorophyll content, experienced a negative impact. This aligns with prior studies that have consistently reported comparable reductions in chlorophyll content and Fv/Fm in various plant species facing drought conditions (Badr and Brüggemann 2020 ; Larouk et al 2021 ). The imposition of DS can result in elevated levels of the enzyme chlorophyllase, subsequently impeding chlorophyll production (Altuntaş et al 2020 ); this phenomenon may be a contributing factor in the observed decrease in chlorophyll levels under DS.…”
Section: Discussionsupporting
confidence: 92%
“…In the presence of drought stress, crucial parameters for photosynthesis in tomato plants, such as Fv/Fm and chlorophyll content, experienced a negative impact. This aligns with prior studies that have consistently reported comparable reductions in chlorophyll content and Fv/Fm in various plant species facing drought conditions (Badr and Brüggemann 2020 ; Larouk et al 2021 ). The imposition of DS can result in elevated levels of the enzyme chlorophyllase, subsequently impeding chlorophyll production (Altuntaş et al 2020 ); this phenomenon may be a contributing factor in the observed decrease in chlorophyll levels under DS.…”
Section: Discussionsupporting
confidence: 92%
“…This in turn led to a significant decline in F v /F m and F v /F 0 , which is indicating damages to PSII due to water deficit (Figure 4). Similar changes in fluorescence parameters were observed in wheat plants subjected to drought [30,31]. PI total (Figure 5B) utilization of light energy because of dissipation through heat, which is in accordance with earlier reports [32].…”
Section: Discussionsupporting
confidence: 91%
“…TRXs are pivotal in facilitating redox reactions, regulating photosynthesis and carbohydrate metabolism, responding to abiotic stresses, and preserving a balanced redox state in organisms under stress [25][26][27]. Notably, chlorophyll content significantly diminishes under drought stress [28]. However, in this study, transgenic plants demonstrated considerably higher chlorophyll levels compared to the control group (Figure 4A).…”
Section: Discussionmentioning
confidence: 52%